Dynamic Susceptibility of Modulated Magnetic Nanowires - Escrig-Murua, J; Saavedra-Díaz, E (American Institute of Physics, 2019)
We have calculated the dynamic susceptibility of modulated permalloy nanowires of 1-μm long and 50 nm diameter using micromagnetic simulations. The resonance modes obtained from these simulations are investigated as functions of both the position of the modulation along the nanowire as well as the size of it. The results presented in this work are important in view of the possible realization of tunable frequency magnonic devices, since we showed that it is possible to adjust a set of frequencies by controlling the geometric parameters of the system. © 2019 Author(s).